On monomiality property of q-Gould-Hopper-Appell polynomials - Nusrat Raza; Mohammed Fadel; Subuhi Khan (Arab Journal of Basic and Applied Sciences)
Recently, in the theory of q-special functions, the extension of the monomiality concept to q-special polynomials is introduced. This extension can be a beneficial tool for considering the quasi-monomiality of certain q-special polynomials. The article intends to reframe the q-Gould Hopper-Appell polynomials via the extension of the monomiality principle concept and establish their properties. Certain examples are considered. Concluding observations are specified for certain results of q-Gould-Hopper-Sheffer polynomials from the viewpoint of the operational identity of q-Gould-Hopper-Appell polynomials.